Teleportasi Kuantum Terkontrol Keadaan Dua-Qubit Sembarang: Agus Purwanto, Lila Yuwana, I Nengah Artawan, Bayu Dwi Hatmoko, Rafika Rahmawati, Achmad Fatih Alqodri - Agus Purwanto Agus Purwanto; Lila Yuwana Lila Yuwana; I Nengah Artawan I Nengah Artawan; Bayu Dwi Hatmoko Bayu Dwi Hatmoko; Rafika Rahmawati Rafika Rahmawati; Achmad Fatih Alqodri Achmad Fatih Alqodri (Jurnal Fisika dan Aplikasinya, 2019)
We have shown in detail a scheme of controlled quantum teleportation of arbitrary two-qubit state via the five-qubit channel which is 30 of 32 measurements of Alice and Charlie give unitary transformations of Bob in positive and negative pairs, the two others are free and different.